2021
DOI: 10.1007/s41030-021-00160-x
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Sarcoidosis Treatment for Pulmonologists

Abstract: Due to frequent lung involvement, the pulmonologist is often the reference physician for management of sarcoidosis, a systemic granulomatous disease with a heterogeneous course. Treatment of sarcoidosis raises some issues. The first challenge is to select patients who are likely to benefit from treatment, as sarcoidosis may be self-limiting and remit spontaneously, in which case treatment can be postponed and possibly avoided without any significant impact on quality of life, organ damage or prognosis. Systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 108 publications
1
16
0
Order By: Relevance
“…However, several studies have shown the effectiveness of biologics to treat sarcoidosis. [30][31][32]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown the effectiveness of biologics to treat sarcoidosis. [30][31][32]…”
Section: Discussionmentioning
confidence: 99%
“…We decided to include sarcoidosis as a PR even though no biologics are approved for the disease. However, several studies have shown the effectiveness of biologics to treat sarcoidosis 30–32 …”
Section: Methodsmentioning
confidence: 99%
“…In a retrospective unblinded uncontrolled cohort study, AZA and MTX yielded similar outcomes [ 47 ]. Reported ADRs are more or less comparable with those of MTX [ 16 ]. Most frequent ADRs include infections, gastro-intestinal complaints, hepatic function decline, pancreatitis, bone marrow depression, as well as fever and fatigue (see also Table 1 ).…”
Section: Second-line Treatmentmentioning
confidence: 99%
“…A recent consensus statement from sarcoidosis experts still endorses glucocorticoids (GCs) as the primary treatment for sarcoidosis, in view of their efficacy and ease of use (low cost and oral administration) [9 ▪ ]. Unfortunately, GCs are associated with a dose-dependent risk of serious ADRs, which tend to accumulate with long-term use (see also Table 1) [1 ▪ ,13–17].…”
Section: First-line Treatmentmentioning
confidence: 99%
“…First-line management for pediatric sarcoidosis includes oral glucocorticoids but the ideal steroid-sparing option is unknown [ 3 ]. Methotrexate, azathioprine, cyclophosphamide, chlorambucil, anti-cytokine biologics and cyclosporine have been utilized in adults with variable efficacy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%